STUDY OF TOPOLOGICAL PROPERTIES OF QUANTUM WELL CDTE/HGTE/CDTE ELECTRONIC STRUCTURES USING THE TIGHT-BINDING METHOD - Gumarilang Cakti Ahmadi, Andi
Zinc blende is a crystal structure that has a very wide potential application in technological development: electronics, photovoltaics, and spintronics. HgTe material is included in the zinc blende structure material which is unique in its electronic structure due to the location of its Fermi Energy which is coincident with the valence band and the conduction band. In addition, HgTe material also has an inversion band structure with P-like Orbital which is above the S-like Orbital. This property is generally not owned by zinc blende structure material. Therefore, by choosing CdTe material which also has a zinc blende structure and is an insulator as a barrier material in the quantum well CdTe / HgTe / CdTe (quantum well HgTe) structure, it is expected that there is a band crossing. This final project will discuss the formulation of tight-binding (TB) and its application to the quantum well HgTe structure. Furthermore, variations in the thickness of HgTe were studied from 8 to 16 layers against fixed 8 layers of CdTe. Band crossing was found in the condition of a critical thickness of HgTe in 11 layers. This is in accordance with previous calculations using the ???? ? ???? perturbation method by Bernervig, et.al. (Science, 2006, pp. 1757-1761). The topological properties were evaluated by calculating Berry curvature at each HgTe thickness variation. The results of the Berry curvature calculation show that there are different forms of Berry curvature between thicknesses below and above thickness. This result is consistent with the topological properties found for quantum well HgTe.